Implementation of Pastry-based P2P system to share sensor data. (28th October 2010) - Seok, Seung-Joon; Song, Wang-Cheol; Choi, Deokjai
With research effort of ubiquitous computing development, wireless sensor networks have also been studied and deployed in many places. Recently, various works for sharing the existing sensor data have been tried. In this paper, we propose a P2P-based system for sharing sensor data. It uses a structured P2P – Pastry to provide DHT-based routing without server and has been deployed in KOREN. We classify the sensor data into real-time data and past data, and Scribe in Pastry is applied to multicast the real-time data and PAST in Pastry is used to store and provide the past data. Also, as Pastry itself does not provide the search function, we propose to use PAST for providing search function using keywords.